Pengaruh Kepuasan Pengguna (EUCS) terhadap Loyalitas Pengguna Spotify di Kalangan Mahasiswa Surabaya - Novan Putra Pratama; Muhammad Andik Izzudin; Ilham Ilham (Jurnal Ilmiah Sistem Informasi, 2026)
The development of music streaming services such as Spotify has increased the need to understand the factors that influence user loyalty, particularly among university students who are highly engaged with digital platforms. Despite the rapid growth in music streaming adoption, research specifically examining the relationship between user satisfaction, measured using the End-User Computing Satisfaction (EUCS) model, and user loyalty among Surabaya university students remains limited. This study aims to examine the influence of the five EUCS dimensions, namely content, accuracy, format, ease of use, and timeliness, on the loyalty of Spotify users. A quantitative research approach was employed, with data collected through a Likert-scale questionnaire distributed to 77 students who have used Spotify for at least three months. The collected data were analyzed using multiple linear regression through SPSS to determine both partial and simultaneous effects of each dimension. The findings reveal that only the ease-of-use dimension has a positive and significant impact on user loyalty, while content, accuracy, format, and timeliness show no significant effects. These results highlight that ease of use plays a crucial role in shaping and maintaining user loyalty among Spotify users in Surabaya. Furthermore, the study provides valuable insights for developers to prioritize usability improvements while also contributing to the enrichment of EUCS-based satisfaction studies in the digital music service domain.